Transient release kinetics of rod bipolar cells revealed by capacitance measurement of exocytosis from axon terminals in rat retinal slices - Oltedal, Leif (Blackwell Science Inc, 2010)
Presynaptic transmitter release has mostly been studied through measurements of postsynaptic responses, but a few synapses offer direct access to the presynaptic terminal, thereby allowing capacitance measurements of exocytosis. For mammalian rod bipolar cells, synaptic transmission has been investigated in great detail by recording postsynaptic currents in AII amacrine cells. Presynaptic measurements of the dynamics of vesicular cycling have so far been limited to isolated rod bipolar cells in dissociated preparations. Here, we first used computer simulations of compartmental models of morphologically reconstructed rod bipolar cells to adapt the ‘Sine + DC’ technique for capacitance measurements of exocytosis at axon terminals of intact rod bipolar cells in retinal slices. In subsequent physiological recordings, voltage pulses that triggered presynaptic Ca(2+) influx evoked capacitance increases that were proportional to the pulse duration. With pulse durations ≤100 ms, the increase saturated at ∼10 fF, corresponding to the size of a readily releasable pool of vesicles. Pulse durations ≥400 ms evoked additional capacitance increases, probably reflecting recruitment from additional pools of vesicles. By using Ca(2+) tail current stimuli, we separated Ca(2+) influx from Ca(2+) channel activation kinetics, allowing us to estimate the intrinsic release kinetics of the readily releasable pool, yielding a time constant of ∼1.1 ms and a maximum release rate of 2–3 vesicles (release site)(−1) ms(−1). Following exocytosis, we observed endocytosis with time constants ranging from 0.7 to 17 s. Under physiological conditions, it is likely that release will be transient, with the kinetics limited by the activation kinetics of the voltage-gated Ca(2+) channels.